Positive affect dysregulation and its relation to binge eating size and frequency - Flynn, Rebecca L.; Massion, Thomas A.; Kosmas, Jacqueline A.; Smith, Shannon R.; Mastronardi, Carli N.; Graham, Andrea K. (Frontiers in Psychology, 2023)
Negative affect is an established predictor of binge eating, yet less is known about positive affect. Low positive affect has been theorized to increase binge eating, but a better understanding is needed on the relationship between positive affect and binge eating frequency and size. Participants were 182 treatment-seeking adults (76% self-identified as female; 45% self-identified their race as Black and 40% as White; and 25% self-identified their ethnicity as Hispanic/Latino) with self-reported recurrent binge eating (≥12 binge episodes in the past 3 months). Participants completed the Positive and Negative Affect Schedule (PANAS) survey and the Eating Disorder Examination to assess frequency of objective binge episodes (OBEs) and subjective binge episodes (SBEs) over the past 3 months. OBEs and SBEs also were combined to yield total binge episodes over the past 3 months. Independent t-tests and linear regression analyses were used to test associations between positive affect scores and binge episode size and frequencies, and to compare low versus higher positive affect on binge frequency. Additional exploratory models were conducted controlling for negative affect, identity characteristics, and socio-demographic variables. Lower positive affect was significantly associated with more frequent total binge episodes, but not OBEs and SBEs when assessed independently. Findings remained consistent when controlling for covariates and when comparing individuals with the lowest versus higher positive affect levels. Overall, results lend support to the theory that low positive affect is associated with binge eating. Increasing positive affect may be an important treatment consideration for those with recurrent binge eating.